2007
DOI: 10.1016/j.cardiores.2006.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Innate immunity and inflammation — New frontiers in comparative cardiovascular pathology

Abstract: Innate immunity and inflammation play key roles in a wide range of pathology - including heart disease and vasculopathies. Current thinking suggests "damage" rather than "foreignness" as the actual trigger of the immune system, which has caused a dramatic change in how we tend to view the etiopathology of most types of heart disease. The future potential of certain anti-inflammatory therapeutic strategies in addressing heart disease is intriguing. Still, the Janus face of immunity/inflammation cannot be over e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
61
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 101 publications
5
61
0
5
Order By: Relevance
“…1,5,[6][7][8][9][10] A substantial body of evidence has demonstrated that acute myocardial infarction (AMI) is associated with inflammation. 8,[11][12][13] Additionally, inflammation has an essential role in myocardial necrosis 7,14) and microvascular reperfusion injury 9) in AMI patients.…”
mentioning
confidence: 99%
“…1,5,[6][7][8][9][10] A substantial body of evidence has demonstrated that acute myocardial infarction (AMI) is associated with inflammation. 8,[11][12][13] Additionally, inflammation has an essential role in myocardial necrosis 7,14) and microvascular reperfusion injury 9) in AMI patients.…”
mentioning
confidence: 99%
“…The development of a SIRS is passed into three stages. The first stage occurs in response to an insult, resulting in a local cytokine response primarily intended to evoke an inflammatory response to promote local cellular repair by recruiting cells from the reticuloendothelial and immune systems [1] [2] [5]. The second stage involves release of small quantities of cytokines into the systemic circulation in order to enhance, or magnify, this local response.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier studies have demonstrated that Adenocin ® show protective effects on severity of SIRS in CHF, caused by toxi-allergic myocarditis in experiments [7] [11] and in patients after bypass graft surgery [4] and congestive heart failure [5]. Moreover, in recent years, was observed that only Adenocin ® in contrast to levosimendan, dobutamine and milrinone increased function capacity index and improve diastolic function of the myocardium in the conditions of maximum pressure overload [12] [13].…”
Section: Introductionmentioning
confidence: 99%
“…Viral infection of the heart is a major cause of acute myocarditis, leading to myocardial inflammation and tissue damage. Cellular infiltration in acute viral myocarditis may be caused by direct cytopathic effects of the virus, pathologic responses to persistent viral replication as well as autoimmunity triggered by the virus (Liu and Mason, 2001;Bowles and Vallejo, 2003;Linde et al, 2007;Rose et al, 2009;Rutschow et al, 2010). The cardiovirulence of the viral agent, together with the host´s genetic susceptibility and the variability in the innate and acquired immune system, appear to determine the extent of the inflammatory reaction, thereby predicting clinical outcome (Kindermann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Upon viral infection of the heart, different signal pathways initiate an inflammatory response and orchestrate the concerted anti-viral defense machinery in a complex manner. Toll-like and RIG-I-like receptors are essential for the recognition of pathogen-associated molecular patterns and their activation induces intracellular signalling pathways which lead to the production of pro-inflammatory cytokines, chemokines, and interferons (Bowles and Vallejo, 2003;Fairweather et al, 2005;Triantafilou et al, 2005;Frantz et al, 2007;Linde et al, 2007;Yajima and Knowlton, 2009;Kawai and Akira, 2010;Takeuchi and Akira, 2010;Yamamoto and Takeda, 2010;Zhu and Mohan, 2010). Vice verse, interferons appear to induce the expression of a subset of toll-like receptors (Khoo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%